2016
DOI: 10.1111/iji.12282
|View full text |Cite
|
Sign up to set email alerts
|

BSHI Guideline: HLA matching and donor selection for haematopoietic progenitor cell transplantation

Abstract: List of recommendations• All laboratories performing H&I testing for allogeneic HPC transplantation should follow EFI standards and be accreditated by EFI and UKAS/CPA. (Grade 1A)• HLA typing definitions as described by Nunes et al. 2011 and here should be used (Grade 1A)• HLA typing results should use official WHO HLA Nomenclature (Grade 1A)• The clinical urgency should be made available to the individual performing the related and unrelated donor search (Grade 1B)• HLA high resolution typing should be perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 119 publications
(163 reference statements)
1
32
0
3
Order By: Relevance
“…One important clinical application of high‐resolution HLA typing is that of matching donors and patients for haematopoietic stem cell transplantation (HSCT). Currently, matching patient and donor ethnicity for HSCT is not a recommendation of the British Society for Histocompatibility and Immunogenetics . However, matching for haplotypes, which are linked to ethnicities, rather than alleles alone could be used to improve clinical outcome after HSCT .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important clinical application of high‐resolution HLA typing is that of matching donors and patients for haematopoietic stem cell transplantation (HSCT). Currently, matching patient and donor ethnicity for HSCT is not a recommendation of the British Society for Histocompatibility and Immunogenetics . However, matching for haplotypes, which are linked to ethnicities, rather than alleles alone could be used to improve clinical outcome after HSCT .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, matching patient and donor ethnicity for HSCT is not a recommendation of the British Society for Histocompatibility and Immunogenetics. 42 However, matching for haplotypes, which are linked to ethnicities, 43 rather than alleles alone could be used to improve clinical outcome after HSCT. 16,44 These data reinforce the argument for full-length gene sequencing as a method of HLA typing, where intronic polymorphisms can be used to infer haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the so‐called lesser expressed HLA loci (LEL) (HLA‐DRB3/4/5, HLA‐DQB1, and HLA‐DPB1), with the exception of HLA‐DQB1 gene and, in some transplant centers HLA‐DPB1 gene, are not routinely typed and therefore not used for the donor/recipient matching for the HSCT. However, the “Guideline for selection and HLA matching of related, adult unrelated donors and umbilical cord units for haematopoietic progenitor cell transplantation” of the British Society for Histocompatibility and Immunogenetics states that HLA‐DRB3, ‐DRB4, and ‐DRB5 typing should be performed and, that in situations when there is a choice between donors who are otherwise equally matched/appropriate, a donor with a smaller number of mismatches at these loci should be chosen . This guideline was introduced because of the investigation performed by Fernandez‐Vina et al who discovered that there is a higher risk of mortality and TRM for patients who, in addition to one mismatch at HLA‐A, ‐B, ‐C, or ‐DRB1 locus, have three or more LEL mismatches in the graft‐vs‐host direction when compared with those with one or no LEL mismatches.…”
Section: The Distribution Of Hla‐drb3 Alleles Among Hla‐drb1*03:01‐pomentioning
confidence: 99%
“…The typing of DRB3/4/5 genes in solid organ transplantation is not an obligatory procedure for the allocation program of Eurotransplant, despite the fact that, due to the peculiarity of the DRB genes, the compatibility for DRB1 genes between the recipient and his donor does not mean that the pair will be identical for the second DRB gene, if that gene is present in the DRB haplotype. At the same time, the typing of null alleles for determining the HLA compatibility in solid organ transplantation is still not mandatory and remains questionable . It is well known that in haplotypes carrying DRB1*04 , DRB1*07 or DRB1*09 alleles, the second active DRB gene is DRB4 .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the typing of null alleles for determining the HLA compatibility in solid organ transplantation is still not mandatory and remains questionable. 1 It is well known that in haplotypes carrying DRB1*04, DRB1*07 or DRB1*09 alleles, the second active DRB gene is DRB4. 2 Sutton et al reported about a DRB4 allele of which no protein product could be detected serologically.…”
Section: Introductionmentioning
confidence: 99%